Chronic adaptations to blood flow restriction aerobic or bodyweight resistance training: A systematic review - Bommasamudram, T.; Morrell, Z. G.; Clarkson, M. J.; Nayak, K. R.; Kadavigere, R.; Russell, A. P.; Warmington, S. A. (Journal of Sports Sciences, 2025)
This systematic review aimed to examine the chronic adaptations of blood flow restriction (BFR) in conjunction with aerobic and bodyweight resistance training. A search of the electronic databases PubMed (MEDLINE), CINAHL, SPORTDiscus® (via EBSCOhost), Embase, and Cochrane (Central) was conducted to identify relevant published studies. The inclusion criteria encompassed a healthy adult sample population (>18 years), original studies, chronic exercise training interventions (minimum 2 weeks duration) employing aerobic BFR exercise or bodyweight resistance BFR exercise, and comparisons with equivalent intensity non-BFR aerobic or bodyweight resistance training. Thirty-three (n = 33) studies met the inclusion criteria and were included in the review. Among the included studies, chronic adaptations to BFR aerobic training were characterized by significant improvements in aerobic capacity (4-9%), muscle strength (6-31%), and muscle hypertrophy (2-11%) compared to non-BFR aerobic training. Furthermore, bodyweight resistance BFR training increased muscle hypertrophy (3-5%) and strength (4-11%). The findings suggest that both aerobic and bodyweight BFR training provide interchangeable options for practitioners prescribing BFR without access to a traditional equipment filled training environment, supporting flexibility in exercise programme design tailored to individual preferences, facility constraints, and specific fitness goals.